Species composition and population dynamics of aphids influencing potato virus Y (PVY) incidence in Karnataka - Kumara, B.B.; Kalleshwara Swamy, C.M.; Shahid, A.; Kadian, M.S.; Venkataravanappa, V. (2017)
The present study was in a traditional potato growing location in Chikkamagaluru, Karnataka state, India. During the two consecutive seasons such as Kharif and Rabi of 2014-2015 observation were recorded, to understand the population dynamics and their influence on potato virus Y incidence. Population dynamics of aphids were studied using sticky trap. A total of five aphid species were observed during Kharif and four species during Rabi on sticky trap. Myzus persicae was found colonizing only on potato. Population was peak at the third week of August with more numbers of aphids (117) on crop per plant and 92 aphids on sticky trap. A fewer aphid population was found colonizing in Rabi compared to Kharif and also very few aphids in sticky traps. Aphid population had positive correlation with maximum temperature, minimum temperature as also on wind speed. Negative correlation was observed with rainfall, morning as well as afternoon humidity in both the seasons. Correlation between aphids and succeeding week per cent PVY incidence showed positive correlation in Rabi season but during Kharif aphids and per cent PVY incidence had negative correlation indicating possibility of infection in the seed itself. Implication of the study of the management of aphids, aphid borne viruses as well as potato seed productions are discussed.